Use of Akulaku Paylater in Islamic Economics (Study on Students of Sharia Economics Study Program, Faculty of Islamic Economics and Business, Sulthan Thaha Saifuddin State Islamic University, Jambi) - Kunnuzi , Kunnuzi; Akbar, Faris; Astuti, Amanda Febri; Subhan, Muhammad; Aprillia, Pita; Iqbal, Muhammad; Nofriza, Eri (International Journal of Economics (IJEC), 2024)
This research aims to explore how people in the Islamic economy feel about the Akulaku app's PayLater feature. And to get a breakdown of how Akulaku PayLater is being utilised. The methodology of this study is qualitative. This research uses observation, interviews, and documentation to gather information. While data visualisation and reduction are used for analysis. According to the findings of this research, Akulaku users can benefit from the convenience of Akulaku PayLater's on-time payment options by taking advantage of the company's bailout funds. Akulaku PayLater continues to impose unnecessary costs on its customers by charging interest on past due balances and other fees with every purchase. The Qardh and Prohibition of Transactions in the Islamic economy state that akulaku PayLater is not permitted because it contains elements that are detrimental to the user, so the app's use is prohibited if it is banned in the Islamic economy.